Photoelectron spectra and high Rydberg states of lithium generated by intense lasers in the over-the-barrier ionization regime - Morishita, Toru; Lin, C. D. (My University, 2013)
We calculated photoelectron energy and momentum spectra and the population of high Rydberg states of lithium atoms by intense 785 nm laser pulses at intensities in the over-the-barrier ionization (OBI) regime. The calculated spectra are compared to experiments reported in Schuricke et al. [Phys. Rev. A 83, 023413 (2011)]. It is shown that in the OBI regime, due to strong depletion of the ground state, the photoelectron spectra are generated from the leading edge of the laser pulse only, resulting in spectra that are nearly independent of laser intensities. Analysis of the calculated spectra reveals that total ionization probability is suppressed as the intensity is increased in the OBI regime. The suppression is due to the increase of excitation probability of high Rydberg states in the OBI regime, demonstrating that atoms and molecules are never fully ionized at high intensities. We also conclude that the interference stabilization model is not needed to explain the formation of high Rydberg states, and that there is no evidence that laser-dressed Kramers-Henneberger states play a role in the strong-field ionization of atoms and molecules by infrared lasers in the OBI regime.